A Secure Authentication Protocol for Internet of Vehicles - Chen, Chien-Ming; Xiang, Bin; Liu, Yining; Wang, King-Hang (IEEE access, 2019)
An Internet of Vehicles (IoV) allows forming a self-organized network and broadcasting messages for the vehicles on roads. However, as the data are transmitted in an insecure network, it is essential to use an authentication mechanism to protect the privacy of vehicle users. Recently, Ying et al. proposed an authentication protocol for IoV and claimed that the protocol could resist various attacks. Unfortunately, we discovered that their protocol suffered from an offline identity guessing attack, location spoofing attack, and replay attack, and consumed a considerable amount of time for authentication. To resolve these shortcomings, we propose an improved protocol. In addition, we provide a formal proof to the proposed protocol to demonstrate that our protocol is indeed secure. Compared with previous methods, the proposed protocol performs better in terms of security and performance.